Comparative genomics of food-derived probiotic Lactiplantibacillus plantarum K25 reveals its hidden potential, compactness, and efficiency - Aziz, Tariq; Naveed, Muhammad; Shabbir, Muhammad Aqib; Sarwar, Abid; Ali Khan, Ayaz; Zhennai, Yang; Alharbi, Metab; Alsahammari, Abdulrahman; Alasmari, Abdullah F. (Frontiers in Microbiology, 2023)
This study aimed to investigate the intricate genetic makeup of the Lactiplantibacillus plantarum K25 strain by conducting a comprehensive analysis of comparative genomics. The results of our study demonstrate that the genome exhibits a high-level efficiency and compactness, comprising a total of 3,199 genes that encode proteins and a GC content of 43.38%. The present study elucidates the evolutionary lineage of Lactiplantibacillus plantarum strains through an analysis of the degree of gene order conservation and synteny across a range of strains, thereby underscoring their closely interrelated evolutionary trajectories. The identification of various genetic components in the K25 strain, such as bacteriocin gene clusters and prophage regions, highlights its potential utility in diverse domains, such as biotechnology and medicine. The distinctive genetic elements possess the potential to unveil innovative therapeutic and biotechnological remedies in future. This study provides a comprehensive analysis of the L. plantarum K25 strain, revealing its remarkable genomic potential and presenting novel prospects for utilizing its unique genetic features in diverse scientific fields. The present study contributes to the existing literature on Lactiplantibacillus plantarum and sets the stage for prospective investigations and practical implementations that leverage the exceptional genetic characteristics of this adap organism.